MANAGEMENT PERSONNEL RECRUITMENT EDUCATION RESOURCES - Masyhari, Fauziah (Entrepreneur, 2012)
Abstract Employees or personnel, especially teachers are the spearhead in the process of Islamic education Islamic education process will not work properly without the teacher's role. Institutionally, the progress of a further education institution is determined by the leadership of these institu tions than others,but in the learning process the teacher plays the most decisive than the method or material. The role of teachers in the learning process is depicted in Arabic phrase has ever delivered A. Malik Fadjar."Al-thoriqohahammu min al-Mudarris Maddah walakin ahmmu minal-thoriqh, the method ismore important than thematerial, but the teacher is more important than a very important role of teachers method. It can be a great potential in promoting or improving the quality of Islamic education, or vice versa. it can also destroy. When the teacher is really valid l and can manage well. Ofcourse they will be more enthusiasm in performing their duties. Even willing to make innovations in learning to achieve success of students. However, if displaced by the act of leader, they could be the most serious obstacle to the process of Islamic education. The attitude of teachers are dependent on the quality of personnel management. It is closely related to the service., management personnel have a specific goal-oriented optimization of work systems in educational institutions. Management personnel or staff aimed to utilize staff effectively and efficiently in order to achieve maximum results, but by staying in pleasant conditions. Keywords: Recruitment, Manpower Education Abstrak Karyawan atau pegawai, terutama guru merupakan ujung tombak dalam proses pendidikan Islam. Proses pendidikan Islam tidak akan berfungsi dengan baik tanpa peran guru. Secara kelembagaan, kemajuan lembaga pendidikan lanjutan ditentukan oleh pimpinan lembaga-lembaga ini daripada yang lain, tetapi dalam proses pembelajaran guru memainkan paling menentukan daripada metode atau materi. Peran guru dalam proses pembelajaran digambarkan dalam frase bahasa Arab yang pernah disampaikan A. Malik Fadjar. "Al-thoriqohahammu min al-al-Mudarris maddah walakin ahmmu minal-thoriqh, metode ini lebih penting daripada materi, tetapi guru lebih penting daripada peran yang sangat penting dari metode guru. Hal ini dapat menjadi potensi besar dalam mempromosikan atau meningkatkan kualitas pendidikan Islam, atau sebaliknya. juga dapat menghancurkan. Ketika guru benar-benar valid l dan dapat mengelola dengan baik. tentu saja mereka akan lebih antusias dalam melaksanakan tugasnya. Bahkan bersedia untuk melakukan inovasi dalam pembelajaran untuk mencapai keberhasilan dari siswa. Namun, jika terlantar akibat tindakan pemimpin, mereka bisa menjadi kendala paling serius bagi proses pendidikan Islam. sikap guru tergantung pada kualitas manajemen personalia. Hal ini erat kaitannya dengan layanan., manajemen personil memiliki optimasi berorientasi pada tujuan spesifik sistem kerja di lembaga-lembaga pendidikan. personil manajemen atau staf yang bertujuan untuk memanfaatkan staf secara efektif dan efisien untuk mencapai hasil yang maksimal, tetapi dengan tetap dalam kondisi yang menyenangkan.Kata kunci: Rekrutmen, Tenaga Kerja Pendidikan